PENGEMBANGAN KOLEKSI SEBAGAI STRATEGI DALAM MENYEDIAKAN SUMBER INFORMASI BERKUALITAS DI PERPUSTAKAAN UII - Muhammad Syukri Al Ghiffary, Ghalib; Rohyanti Zulaikha, Sri (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2025)
This study aims to analyze the strategy for developing UII library collections in supporting the Tri Dharma of Higher Education. As an institution that plays a central role in the provision of information, libraries are required to have relevant, up-to-date collections and are able to meet the academic needs of users. However, at the UII library, a policy review was carried out in 2018. Delays in updating these policies have the potential to create a gap between the growing needs of user information and the collections available. This research uses a descriptive qualitative approach with a case study method that involves in-depth interviews with librarians as well as direct observation and analysis of collection development policy documents. The results of the study show that the UII library implements several strategic stages in the development of collections including selection based on the needs of the study program, collaboration between lecturers and libraries, and the use of various information sources to identify suitable collections. Challenges such as budget constraints and rapid changes in science require libraries to remain adaptive and responsive to user needs.